DIPLOMASI INDONESIA TERHADAP PEMERINTAH HONG KONG DALAM MENANGANI KASUS PMI OVERSTAY TAHUN 2017-2020 - Aditya Arhammar Didi Riyanto, (2022)
Indonesia has a large population and can be a potential for developing the country. However, this is not in line with the lack of equal distribution of employment opportunities in Indonesia, which causes a large number of unemployment and poverty. This has made Indonesia carry out a policy of sending Indonesian Migrant Workers abroad where Indonesia has labor relations with many countries, one of which is Hong Kong because there are many Indonesian Migrant Workers who have chosen to work in Hong Kong over the last few years. The large number of Indonesian migrant workers working in Hong Kong then makes the Indonesian Government also have to make policies to protect Indonesian Migrant Workers in Hong Kong from various cases that can occur, such as cases of overstay. One of the steps taken by the Government of Indonesia is to hold a meeting with the Hong Kong party to make a work contract regulation for a maximum of 2 (two) years with an option to extend the contract. Unfortunately, the application of these regulations contradicts the fact that overstay cases continue to afflict Indonesian Migrant Workers in Hong Kong where in the last 5 (five) years there have been more than 400 (four hundred) cases so that Indonesia must carry out diplomacy to deal with this. The author uses 2 (two) frameworks of thought in this research, namely Migration and Diplomacy. In this study, the author uses a qualitative approach and a descriptive type of research which uses 2 (two) sources of data, namely primary data and secondary data. The results of the study stated that Indonesia's diplomacy to the Hong Kong Government in handling the Indonesian Migrant Workers overstay case was in the form of protection diplomacy carried out in various ways, both preventive and reactive.